Transitional cell carcinoma of the renal pelvis masquerading as renal tuberculosis - Lalhruaizela, Samuel; Zadeng, Zothansanga; Hruaitluanga, Lal (International Surgery Journal, 2020)
We report a case of transitional cell carcinoma of the right renal pelvis mimicking the signs, symptoms and radiological findings of renal tuberculosis (TB). She had been diagnosed initially for urinary tract infection and radiological diagnosis initially was more towards renal TB and urine cytology and cultures were normal. Specific investigations for tuberculosis all showed negative results. But as neoplasia could not be ruled out by ureterorenoscopy due to presence of multiple ureteric strictures, decision was taken for an exploratory surgery. During surgery it was found that there was a tumour in the upper pole of kidney involving the renal pelvis and was found to be papillary transitional cell carcinoma on histopathological examination.